2021
DOI: 10.3390/nu13051633
|View full text |Cite
|
Sign up to set email alerts
|

Creatine in T Cell Antitumor Immunity and Cancer Immunotherapy

Abstract: Creatine is a broadly used dietary supplement that has been extensively studied for its benefit on the musculoskeletal system. Yet, there is limited knowledge regarding the metabolic regulation of creatine in cells beyond the muscle. New insights concerning various regulatory functions for creatine in other physiological systems are developing. Here, we highlight the latest advances in understanding creatine regulation of T cell antitumor immunity, a topic that has previously gained little attention in the cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 105 publications
0
11
0
Order By: Relevance
“…In this sense, the human muscle transcriptome analysis performed by Safdar et al [ 70 ] demonstrated that a 10-day CrM supplementation period decreased the phosphofructokinase mRNA content by 21% versus placebo. For a recent review on the role of Cr in T cell anti-tumor immunity and cancer immunotherapy, please refer to Li and Yang [ 127 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the human muscle transcriptome analysis performed by Safdar et al [ 70 ] demonstrated that a 10-day CrM supplementation period decreased the phosphofructokinase mRNA content by 21% versus placebo. For a recent review on the role of Cr in T cell anti-tumor immunity and cancer immunotherapy, please refer to Li and Yang [ 127 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the metabolic and ergogenic properties of CrM [ 7 , 14 , 15 , 24 ], there has also been interest in assessing the effects of CrM supplementation in various clinical populations that may benefit from increasing high-energy phosphate availability and/or increasing strength and muscle mass [ 5 ]. A recent Special Issue on creatine supplementation for health and clinical diseases overviewed the metabolic basis of creatine in health and disease [ 5 ] and potential health and/or therapeutic benefits of CrM supplementation for pregnancy and newborn health [ 146 ], children and adolescents [ 147 , 148 , 149 , 150 , 151 ], physically active young adults [ 24 ], rehabilitation [ 152 ], women’s health [ 133 ], older adults [ 44 ], brain health and cognitive function [ 74 ], glucose management and diabetes mellitus [ 153 ], immunity [ 154 ], T cell antitumor immunity and cancer therapy [ 155 ], heart health [ 156 ], vascular health [ 157 ], inflammatory bowel disease [ 158 ], chronic renal disease management [ 159 ], and post-viral fatigue [ 160 ]. From what we can see, all studies in these populations used CrM as the source of creatine.…”
Section: Strong Evidence To Support Bioavailability Efficacy and Safetymentioning
confidence: 99%
“…The possible anti-inflammatory effects of creatine have been evaluated in models of disease associated with inflammation such as cancer [ 38 , 41 ]. Here, the researchers gave rats with tumor cells creatine ( n = 10; 300 mg⋅kg −1 ⋅day −1 ) or placebo ( n = 9; water) via intragastric gavage and compared this to a control condition ( n = 6).…”
Section: Anti-inflammatory Effects Of Creatine Supplementationmentioning
confidence: 99%
“…Supporting these findings, Di Biase et al in 2019 [ 42 ] identified that supplementing mice with creatine (10.5 mg daily for injection based administration and 3 g⋅kg −1 ⋅day −1 for diet based administration) slowed tumor growth determined by measurement with digital calipers ( n = 3–4), and that creatine was an important metabolic regulator of antitumor CD8 T cell immunity ( n = 3–9) quantified with quantitative polymerase chain reaction for creatine transporter, flow cytometry analysis or western blot analysis. Taken together, it appears that creatine has the potential to suppress tumor growth and improve T cell-based immunotherapies for cancer treatment [ 38 , 41 , 42 ].…”
Section: Anti-inflammatory Effects Of Creatine Supplementationmentioning
confidence: 99%